Adsorption of Organic Dye Methylene Blue on Activated Carbon Prepared from Wood - Elmerzouki, Khadija; Bimaghra, Itto; Sahlaoui, Ahmmed; Lghazi, Youssef; Ait himi, Mohamed (International Journal of Engineering and Technology, 2018)
Developing countries are the most exposed to pollution problems. To cope, they must develop integrated environmental management policies (water management, air treatment, treatment of industrial effluents, etc.). As a result, different treatment methods must be used to reduce these problems. This work aimed to evaluate the feasibility of fixing organic dye such as methylene blue using activated carbon (ACW) prepared from inexpensive precursor (sawdust) by chemical and thermal activation. The adsorption efficiency depends on several parameters such as the initial pH of the solution, the contact time and the mass of ACW. The adsorption isotherms were studied according to the Freundlich and Langmuir models, and the best was chosen on the basis of the comparison of their correlation coefficient results. Â Â